Penyelesaian Sengketa di Dalam Hukum Pasar Modal - Harahap, Aprilinda M.; Sirait, Nadilla; Sari,, Dessy Indah; Sitorus, Andini Cahayani; Hasibuan, Haris Fadila; Ayusri, Ari; Sitorus, Arina Rofiqoh; Bakti, Bakti; Siregar, Emiel Salim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The capital market is an organized financial system that brings together shareholders and investors who have a certain period of time, either directly or through intermediaries. The capital market sector is one of the financial services sectors that play an important role in national development. At present, there are many criticisms of capital market dispute resolution caused by many factors related to law enforcement, so that efforts to create an orderly and efficient capital market have not been optimally achieved. In writing this research the method used refers to normative juridical, which contains many juridical reviews from several sources and references to the object under study. In writing this article, a juridical approach is used to get conclusions and keywords that are very precise from the object of study in this article. Keywords : Capital Market, Dispute Resolution.